2022
DOI: 10.1016/j.ymssp.2021.108706
|View full text |Cite
|
Sign up to set email alerts
|

The periodically extended stiffness nonlinear energy sink

Abstract: Conventional nonlinear energy sinks (NES) are considered to be a more robust alternative to linear vibration absorbers such as the tuned-mass-damper (TMD). While the conventional NES has a larger efficient frequency bandwidth than the TMD, it is only really efficient for a small energy range. This implies a deterioration of the NES's mitigation properties if the primary system's amplitude varies. To overcome this issue, other researchers resort to increasing the complexity of the NES by adding degrees-of-freed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 35 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…In Type I, II and III, the high performance is only achieved at or near the input energy used for optimization of the NES parameters which limits their application. Therefore, stiffness-based NESs performance has been enhanced by employing hardening and softening in the nonlinear coupling element [68], employing unsymmetrical nonlinear coupling force [69,70], or by including negative linear or nonlinear stiffness content in the coupling nonlinear force [71][72][73][74][75][76][77]. This has resulted in substantial enhancement in the performance of the NES even at high intensity impulsive loadings [73].…”
Section: Stiffness-based Nessmentioning
confidence: 99%
“…In Type I, II and III, the high performance is only achieved at or near the input energy used for optimization of the NES parameters which limits their application. Therefore, stiffness-based NESs performance has been enhanced by employing hardening and softening in the nonlinear coupling element [68], employing unsymmetrical nonlinear coupling force [69,70], or by including negative linear or nonlinear stiffness content in the coupling nonlinear force [71][72][73][74][75][76][77]. This has resulted in substantial enhancement in the performance of the NES even at high intensity impulsive loadings [73].…”
Section: Stiffness-based Nessmentioning
confidence: 99%
“…its natural frequency tends to a constant value. Considering possible practical realizations of a softening NES, in [25,36,38] a device was presented that can tailor-make stiffness characteristics. It would not be able to achieve sgn(x a ) 3 |x a | because of its infinity derivative; therefore, to facilitate computation and future experimental works, the softening and saturation arctan function will be used later on to showcase inverted resonance cascade, as its frequency-energy relation is very similar to the sgn(x a ) 3 |x a | function.…”
Section: Frequency-amplitude Plot Of An Nes With Softening Stiffnessmentioning
confidence: 99%
“…where A h (T ), B j (T ) ∈ C, * stands for complex conjugate and z j is the contribution of mode j to z. Deriving 2A h (T )e iω h T = q h − i qh /ω h and 2B j (T )e jωj T = z j − i żj /ω j yields, after some steps [36]:…”
Section: Slow Invariant Manifold and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, NES has recently attracted the continuous attention of many researchers [11]. Dekemele et al proposed a periodically extended stiffness NES; their results demonstrated that the periodically extended stiffness could overcome the disadvantage of the small effective energy range of the traditional NES [12]. The instantaneous model makes the system coupled with the vibro-impact (VI) NES fall into nonphysical chaotic states.…”
Section: Introductionmentioning
confidence: 99%